A College of Business Administration as a Production System - Bell, Eugene C. (Academy of Management Journal, 1974)
Two contrasting models, factory and service, are developed from general systems theory and used to describe the college production process. Issues explored in terms of the models are: open admission, research, facility location, training versus education, instructional methods, academic freedom, instructor evaluation, and the college's responsibility in placement.